Influence of Different Antiseizure Medications on Vascular Risk Factors in Children with Epilepsy - Doaa M. Mahrous; Asmaa N. Moustafa; Mahmoud M. Higazi; Aliaa M. Higazi; Reem A. AbdelAziz (Children, 2022)
Many studies have proposed that plasma homocysteine levels are increased as a side effect with the prolonged use of antiseizure medications. This is associated with an increase in carotid intima media thickness; hence, it increases the threat of atherosclerosis at a young age. We aimed to assess serum levels of homocysteine in epileptic children on long-standing antiseizure medications and its association with increased occurrence of cardiovascular disease. The study included 60 epileptic children aged between 2 and 15 years old who visited our pediatric neurology outpatient clinic and 25 apparently healthy children served as a control group. All included children were subjected to careful history taking, clinical examination, anthropometric measures, laboratory investigations including serum homocysteine levels and lipid profile, along with radiological assessment involving carotid intima media thickness and carotid stiffness. Results demonstrated a significant increase in the serum levels of homocysteine, carotid intima media thickness, and carotid stiffness in children on monotherapy of old generation antiseizure medications and polytherapy than that in children on monotherapy of new generation antiseizure medications and control children. Epileptic children on old generation and polytherapy antiseizure medications have an increased risk for cardiovascular diseases and need follow up for early intervention when needed.